1999
DOI: 10.1002/(sici)1097-0215(19991022)84:5<470::aid-ijc4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production and activation of matrix metalloproteinase-7 (matrilysin) in human endometrial carcinomas

Abstract: We examined production and tissue localization of 7 different matrix metalloproteinases (MMP‐1, ‐2, ‐3, ‐7, ‐8, ‐9 and ‐13) and 2 tissue inhibitors of metalloproteinases (TIMP‐1 and ‐2) in human endometrial‐carcinoma tissues. Sandwich enzyme immunoassays showed enhanced production of MMP‐7, MMP‐8 and MMP‐9 as well as TIMP‐1 in the carcinoma tissues compared with non‐carcinoma endometrial tissues. Among these MMPs, only the amount of MMP‐7 correlated with clinicopathological factors of the carcinomas. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 24 publications
2
50
1
1
Order By: Relevance
“…However, no studies have elucidated the molecular mechanism regulating MMP-7 localization to the basal epithelial compartment or the depolarized diffuse cytoplasmic distribution of MMP-7 in adenocarcinoma cells at the invasive front. Similar to other MMPs such as MMP-2, the activated form of MMP-7 is readily detected within both carcinoma 11,17 and normal intestinal tissues. 6 Our previous in vitro biochemical studies have shown that proMMP-7 is fully activated by treatment with trypsin or MMP-3, and partially with plasmin or leukocyte elastase.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…However, no studies have elucidated the molecular mechanism regulating MMP-7 localization to the basal epithelial compartment or the depolarized diffuse cytoplasmic distribution of MMP-7 in adenocarcinoma cells at the invasive front. Similar to other MMPs such as MMP-2, the activated form of MMP-7 is readily detected within both carcinoma 11,17 and normal intestinal tissues. 6 Our previous in vitro biochemical studies have shown that proMMP-7 is fully activated by treatment with trypsin or MMP-3, and partially with plasmin or leukocyte elastase.…”
mentioning
confidence: 82%
“…Importantly, there is a large difference in the distribution of MMP-7 between adenomas and adenocarcinomas; MMP-7 is predominantly immunolocalized to the apical surface of dysplastic glands of the adenomas, 7 whereas the cytoplasm of carcinoma cells at the invasive front is diffusely immunostained in human gastrointestinal and endometrial carcinomas. 11,14 Thus, the data, together with the broad range of substrate specificity of MMP-7, 3,15 suggest the possibility that different functions of this proteinase under various pathophysiological conditions may be dictated by vectorial secretion of MMP-7. Yu et al 16 have demonstrated that CD44 heparan sulfate proteoglycan (CD44HSPG), which is selectively expressed on the apical site of gland cells, anchors active MMP-7 to the lumenal site of postpartum uterine and lactating mammary gland epithelium in normal mice, but that in CD44 À/À mice MMP-7 is redistributed from the apical to the basal compartment of the epithelia.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Many laboratories have shown that MMPs are overexpressed in cancers and play an important role in cancer invasion and metastases (25)(26)(27). In particular, MMP7 is upregulated in endometrial, gastric, and colorectal cancers, and the MMP7 activity correlates with vascular invasion and metastases (28)(29)(30). Thus, MMPs that mediate the cleaving of FasL could be expressed on the tumor cells and/or present within the ocular and hepatic environment.…”
Section: Discussionmentioning
confidence: 99%